Analyzing Skill Profile Among Business Graduates: Is it Generic or Specific? - Wye, Chung-Khain; Lim, Yet-Mee (International Journal of Business, Economics and Management, 2014)
Empirical studies on skill profile required at the workplace have focused on individual job function and industry per se. These studies may have ignored the potential heterogeneity of skill requirement across job functions and industries. Some of the skills may be occupation-specific, industry-specific or generically applicable across occupations and industries. Based on a Malaysian case study on 45 managers of five different job positions who had experience in job recruitment in six different industries, this study shows that not only are skills and abilities, personal attributes, and content knowledge statistically specific to industry and job, some of the characteristics in these aspects are generically applicable to all industries and jobs.